The Role of Inflammatory Pathways in the Development of Rosacea - Sieradocha, Kamila; Jedlikowska, Wiktoria; Furlepa, Natalia (Journal of Education, Health and Sport, 2024)
Rosacea is a prevalent yet poorly understood chronic inflammatory skin condition, characterized by symptoms such as flushing, erythema, papules, and telangiectasia. Although the precise causes of rosacea remain unclear, its pathogenesis involves complex interactions between genetic, environmental, microbial, and immune factors. Recent studies highlight a crucial role for both the innate and adaptive immune systems, implicating Toll-like receptors, neutrophils, macrophages, and cytokines as central to the inflammatory cascade seen in rosacea. Additionally, the overexpression of molecules like cathelicidin and vascular endothelial growth factor (VEGF) contributes to the disease's hallmark features, such as vasodilation and angiogenesis. Trigger factors including UV radiation, dietary components, and microbial influences further exacerbate inflammation, underscoring the multi-factorial nature of the condition. Traditional treatment options, like topical metronidazole, azelaic acid, and oral tetracyclines, have demonstrated efficacy in controlling mild to moderate cases of rosacea. However, more severe cases remain challenging to treat, prompting exploration into novel therapies like IL-17 inhibitors, laser therapy, and probiotics. This review investigates the inflammatory pathways central to rosacea pathogenesis and evaluates emerging therapeutic approaches aimed at addressing the underlying mechanisms of this condition. Understanding these pathways may lead to more effective treatment strategies, improving patient outcomes and quality of life.